Topo[graphies] of the Un/conscious - Martin, Bea (Architecture Image Studies, 2020)
The topography that entertains the unconscious includes inhabitants and the forms of their passage through spaces. A landscape of vessels, a place that both “holds and moves”. This is an e-motional field, where the topographic relationships of component parts are not stable and fixed; rather, they can be mis-placed, dis-placed, or even re-placed. The type of topography foregrounded here is a projected landscape of the unconscious. A field through which all our experiential memories are mediated – a ‘field of being’. This article explores how architectural space registers in such a field. The narrative is assembled as a montage of verbal and visual constructs and routing in the form of mental frames. This includes a graphic exploration of cognitive processes and their visual representation, a structural mapping of mental space through frames and folds of memory, as well as the tectonic field in which the psychoanalytic encounter between narrator and narrative takes place on a drawing.